The Influence of Financial Inclusion and Financial Technology on MSME Performance in Garut Regency - Wufron, Wufron; Susilawati, Wati; Handayani, Wulan S (Fakultas Ekonomi Universitas Garut, 2024)
The purpose of this study is to understand and analyze the impact of financial inclusion and FinTech on the performance of MSMEs in Garut Regency. This research uses a quantitative approach. The population consists of MSME actors in Garut Regency. The sample size used in the study is 100 respondents. Data collection techniques include questionnaires and interviews. Data analysis combines descriptive statistical analysis with multiple linear regression. Data was processed using IBM SPSS Statistics version 26. The study's findings indicate that financial inclusion has a positive and significant impact on the work performance of MSME employees. FinTech also has a positive and significant effect on MSME employee performance.